2012
DOI: 10.1638/2011-0265r.1
|View full text |Cite
|
Sign up to set email alerts
|

SUSPECTED NEUROTOXICITY DUE TOCLOSTRIDIUM PERFRINGENSTYPE B IN A TIGER (PANTHERA TIGRIS)

Abstract: A 4-yr-old tiger (Panthera tigris) was referred with acute onset of severe abnormal consciousness. Neurological evaluation showed normal palpebral and corneal reflexes, normal pupil diameter with normal direct and consensual papillary light reflex, and absent menace response bilaterally. Diffuse forebrain lesion or focal lesion affecting the ascending reticular activating system was suspected. Complete blood examination and cerebrospinal fluid analysis were normal. Magnetic resonance imaging of the brain showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…Aliquots of 10μl of each dilution were plated on sulfite polymyxin sulfadiazine agar (Difco Laboratories, Detroit, MI, USA) and were anaerobically incubated at 37°C for 24 hours. After incubation, all sulfatereducing colonies from each dilution were subjected to a previously described PCR protocol (Vieira et al, 2008) for the detection of genes encoding the major C. perfringens toxins (alpha, beta, epsilon and iota), beta-2 toxin (cpb2) and enterotoxin (cpe). The PCR protocol described by Keyburn et al (2008) and Gohari et al (2015) was applied for the detection of the NetB-and NetF-encoding genes (netB and netF, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…Aliquots of 10μl of each dilution were plated on sulfite polymyxin sulfadiazine agar (Difco Laboratories, Detroit, MI, USA) and were anaerobically incubated at 37°C for 24 hours. After incubation, all sulfatereducing colonies from each dilution were subjected to a previously described PCR protocol (Vieira et al, 2008) for the detection of genes encoding the major C. perfringens toxins (alpha, beta, epsilon and iota), beta-2 toxin (cpb2) and enterotoxin (cpe). The PCR protocol described by Keyburn et al (2008) and Gohari et al (2015) was applied for the detection of the NetB-and NetF-encoding genes (netB and netF, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, the small risk degree which its application entails might allow us to justify its use in these endangered species. With developing technology in zoos and wildlife rehabilitation centres, MRI is a promising, noninvasive, and accurate method for tiger imaging [17][18][19][20][21]. Our research provides the first anatomical description of the elbow in a Bengal tiger (Panthera tigris tigris) via low-field MRI.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, MRI has been only used to describe the normal anatomic features of the stifle and tarsus joints [17,18], as well as brain characteristics [19]. Also, previous reports describing several neurological disorders have been published on this species [20,21]. However, no published studies were found describing the Bengal tiger elbow joint using MRI and gross anatomical dissections.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of C. perfringens as a pathogen for humans and animals, the role of this agent in wild carnivores remains unknown. The current understanding of C. perfringens pathogenicity is based on reported cases of hemorrhagic enterocolitis and nervous disorders (ZEIRA et al, 2012).…”
mentioning
confidence: 99%
“…However, these studies only assessed isolates from a single animal species and were restricted to strains from domestic animals. Thus, recent reports have highlighted the need for an empirical analysis of the most effective antimicrobial for treating C. perfringens infections in wild animals (ZEIRA et al, 2012).…”
mentioning
confidence: 99%